Treatment satisfaction in 5q-spinal muscular atrophy under nusinersen therapy. (March 2021) - Osmanovic, Alma; Ranxha, Gresa; Kumpe, Mareike; Wurster, Claudia D.; Stolte, Benjamin; Cordts, Isabell; Günther, René; Freigang, Maren; Müschen, Lars H.; Binz, Camilla; Hermann, Andreas; Deschauer, Marcus; et al.
Background: Nusinersen was the first approved disease-modifying therapy for all 5q-spinal muscular atrophy (SMA) patients regardless of age or disease severity. Its efficacy in adults has recently been demonstrated in a large cohort by motor outcome measures, which were only partially suitable to detect changes in very mildly or severely affected patients. Patient-reported outcome measures (PROs) have been suggested as a valuable addition. Here, we aimed to assess treatment satisfaction and investigate whether it may be a useful PRO to monitor SMA patients. Methods: We enrolled 91 mainly adult 5q-SMA patients treated with nusinersen in a national, multicenter, cross-sectional observational study. 21 patients underwent longitudinal follow up. Patients' satisfaction with treatment in four dimensions (global, effectiveness, convenience, side effects) was assessed by the Treatment Satisfaction Questionnaire for Medication German version 1.4 (TSQM-1.4 © ) and related to clinical parameters, motor scores, and treatment duration. Results: More than 90% of SMA patients were consistently satisfied over a median treatment duration of 10 months. Highest mean scores were observed in the dimensions 'side effects, ' 'global satisfaction, ' and 'effectiveness' (93.5 ± 14.8 versus 73.1 ± 21.0 and 64.8 ± 20.6, respectively). Patients' satisfaction with the convenience of treatment was considerably lower (43.6 ± 20.2). Interestingly, satisfaction with the effectiveness was higher in ambulatory ( p  = 0.014) compared with non-ambulatory patients and directly correlated to motor outcome measures. Five non-ambulatory patients withdrew from therapy. All of them presented with a deterioration of motor outcome measures and reported dissatisfaction with treatment effectiveness and convenience. Conclusion: Most patients were satisfied with nusinersen treatment effectiveness. Less severely affected patients indicated higher satisfaction. The TSQM-1.4 © helped to identify therapy non-responders, who mainly addressed dissatisfaction with effectiveness and convenience. We suggest introducing the TSQM-1.4 © as an additional PRO in SMA into clinical practice.